Determining the optimal route in the network of tourist attractions of the City of Pula - Kostelić, Katarina; Cvek, Loris; Draženović, Marjan; Drezga, Luka; Grbac, Axel; Pajković, Matteo (Oeconomica Jadertina, 2021)
This paper evaluates the optimal route of tourist attractions in the City of Pula. By modelling the route over ten chosen tourist attractions in Pula and through application of evolutionary method as travelling salesman problem (TSP), it was proven that such approach can be used for determining optimal routes of tourist attractions. The problem was set as a walking route and modelled from theperspectives of tour distance minimization and tour time minimization. Model representation and solving using MS Excel points out to the possibility of simple and intuitive data preparation and analysis, as well as relatively quick solution output. The results indicate their possible use in tour organization within touristic destination, the pros and cons of the used method, but also point out to the advantages of using quantitative methods in tourist attraction management. The observed flexibility of the solution application revealed possibilities for further model development, as well as possible integration in the support system based on the quantitative methods for managing destinations with the aim of tourism destination sustainability.
Keywords: optimal route; quantitative methods; network models; TSP; evolutionary method; Solver; tourism attractions; tourism destination management